DINAMIKA HIBAH DAN WARIS: TINJAUAN TERKINI DAN IMPLIKASINYA DALAM PRAKTIK HUKUM DI INDONESIA - Jamiluddin, Amir (Universitas Kiai Abdullah Faqih Gresik, 2024)
Abstract: This study aims to explore the current dynamics in grant and inheritance law in Indonesia and analyze their implications for legal practice. Grant, which is a voluntary gift of property by a person to another during his or her lifetime, and inheritance, which relates to the division of property after death, play an important role in the regulation of wealth and property rights. The complexity of the laws governing grants and inheritance in Indonesia, which include Western civil law, Islamic law, and customary law, often leads to confusion and disputes. This research methodology uses a qualitative approach through literature study and legal document analysis. Data was obtained from laws and regulations, scientific journals. The research identified key challenges in the application of grant and inheritance law, such as differences in legal interpretation, legal uncertainty, and the need for clear documentation. The results show that recent legal developments have focused on increasing awareness of the importance of valid documentation to reduce disputes as well as efforts to harmonize the various applicable legal systems. Implications for legal practice include the need for improved understanding and compliance with existing regulations, as well as better access to legal information for the public. This research provides useful insights for legal practitioners, academics, and policy makers in understanding the dynamics of grants and inheritance and their implications in legal practice in Indonesia. Thus, this research is expected to contribute to the improvement of legal certainty and justice in grant and inheritance cases. Keywords: hibah, waris, praktik hukum, hukum diindonesia